Different approaches to reduce shaft voltage in AC generators - zare, F.; Abadi, J.; Ghosh, Arindam (2009 13th European Conference on Power Electronics and Applications (EPE 2009), 2009)
This paper presents several shaft voltage reduction techniques for doubly-fed induction generators in wind turbine applications. These techniques includes: pulse width modulated voltage without zero vectors, multi-level inverters with proper PWM strategy, better generator design to minimize effective capacitive couplings in shaft voltage, active common-mode filter, reducing DC-link voltage and increasing modulation index. These methods have been verified with mathematical analysis and simulations.